Enzymatic modification of grapeseed (Vitis vinifera L.) oil aiming to obtain dietary triacylglycerols in a batch reactor. (January 2019) - Bassan, Natalia; Rodrigues, Rafael Hatanaka; Monti, Rubens; Tecelão, Carla; Ferreira-Dias, Suzana; Paula, Ariela V.
Abstract: Structured lipids (SL) are chemically or enzymatically modified oils and fats with respect to their original fatty acid composition or position in acylglycerols. These compounds present improved functional or nutraceutical properties. The present work aimed at the enzymatic synthesis of SL, MLM-type dietary triacylglycerols, that is, those with medium chain fatty acids (M) at the sn -1 and sn -3 positions, and long chain fatty acids (L), in the internal position of the triacylglycerol. Grapeseed oil was selected based on its composition rich in unsaturated fatty acids, principally linoleic acid. This oil was submitted to batch acidolysis with medium chain fatty acids (caprylic or capric) in solvent-free media. Reactions were catalyzed by different immobilized commercial lipases, namely: Lipozyme TL IM ® ( Thermomyces lanuginosa lipase), Lipozyme RM IM ® ( Rhizomucor miehei lipase) and Novozym 435 ® ( Candida antarctica lipase B). The incorporation degree (ID) ranged from 23.62 ± 1.34 to 34.53 ± 0.05 mol%, after 24 h reaction at 45 °C, using a molar ratio (MR) fatty acid:oil of 2:1. The best results were obtained using capric acid and Lipozyme RM IM ® lipase (34.53 ± 0.05 mol%). In the experimental design, the influence of MR and temperature on ID were evaluated. ID increased with MR and T and was fitted to a saddle-like surface. Highlights: Enzymatic acidolysis reactions in batch reactors employing medium chain fatty acids. Structured lipids (MLM-type dietary triacylglycerols), from grapeseed oil. Incorporation degree of fatty acid: ranged from 23.62 ± 1.34 to 34.53 ± 0.05%. Best results: capric acid and Lipozyme RM IM lipase. Only linear molar ratio had a significant influence on the incorporation degree.